Retrospective Analysis of Hairy Cell Leukemia Patients Treated with Different Modalities as First Line: Real-Life Experience Over 20 years - (:unkn) unknown (SPRINGER INDIA, 2019)
We aimed to analyze the characteristics and response rates of different treatment modalities in hairy cell leukemia patients over 20 diagnosed as hairy cell leukemia (HCL). Clinical data, response rates and survival outcome of the patients who were diagnosed with HCL were retrospectively analyzed. Fifty-two patients with a median age of 50 (28-87) years were enrolled in the study. 38 patients (73%) were male and male to female ratio was 2.7. First line therapy was cladrabine in 36 patients (69.2%). The overall response rate was 97%. CR and PR rates were 86.1% and 11.1%, respectively. Interferon was used in 10(19.2%) patients who were diagnosed before 2000s years. CR and PR rates were 70% and 30%, respectively. Although the CR rates were lower in IFN group, this difference could not be reached statistically significance (p = 0.24). The median follow up was 48 months (12-252). The median OS was not reached and median PFS was 150 months (95% CI, 116-214). The OS at 36 and 48 months were 95.9% and 92.3%, respectively and the PFS at 36 and 48 months were 90.2% and 83.4%, respectively. After the introduction of purine analogues, the fate of the HCL patients have been changed. Cladrabin achieved very high response rates in both young and older patients, in our study. Although relapse still constitutes a problem, another single dose of cladrabine results in good response rates.
Keywords: Hairy cell leukemia; Cladrabin; Treatment; Survival rates; Response rates; TERM-FOLLOW-UP; 2-CHLORODEOXYADENOSINE 2-CDA; CLADRIBINE; PENTOSTATIN; DIAGNOSIS; OUTCOMES